Helicobacter pylori antibody responses and evolution of precancerous gastric lesions in a Chinese population. Issue 9 (7th November 2013) - Pan, Kai‐Feng; Formichella, Luca; Zhang, Lian; Zhang, Yang; Ma, Jun‐Ling; Li, Zhe‐Xuan; Liu, Cong; Wang, Yu‐Mei; Goettner, Gereon; Ulm, Kurt; Classen, Meinhard; You, Wei‐Cheng; et al.
<x xml:space="preserve">Abstract</x> Helicobacter pylori‐specific proteins are involved in gastric carcinogenesis. To investigate the seroprevalence of six H. pylori‐specific antibodies in patients with different gastric histology, and the impact of seropositivities on the evolution of precancerous gastric lesions, a follow‐up study was conducted in Linqu County, China. The seropositivities for CagA, VacA, GroEL, UreA, HcpC and gGT were assessed by recomLine analysis in 573 H. pylori‐positive subjects and correlated with evolution of precancerous gastric lesions. We found that the score of H. pylori recomLine test was significantly increased in subjects with chronic atrophic gastritis (CAG, p < 0.0001) or intestinal metaplasia (IM, p = 0.0125), and CagA was an independent predictor of advanced gastric lesions, adjusted odds ratios (ORs) were 2.54 (95% CI = 1.42–4.55) for IM and 2.38 (95% CI = 1.05–5.37) for dysplasia (DYS). Moreover, seropositivities for CagA and GroEL were identified as independent predictors for progression of gastric lesions in a longitudinal study, and ORs were 2.89 (95% CI = 1.27–6.59) and 2.20 (95% CI = 1.33–3.64), respectively. Furthermore, the risk of progression was more pronounced in subjects with more than three positive antigens (pfor trend = 0.0003). This population‐based study revealed that seropositivities for CagA and GroEL might be potential markers to identify patients infected with high‐risk H. pylori strains, which are related to the development of GC in a Chinese high‐risk population, and recomLine test might serve as a tool for risk stratification.